2020
DOI: 10.1007/s42990-020-00038-1
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the lithosphere and upper mantle beneath the Eastern Mediterranean and Middle East

Abstract: Surface velocity measurements show that the Middle East is one of the most actively deforming regions of the continents. The structure of the underlying lithosphere and convecting upper mantle can be explored by combining three types of measurement. The gravity field from satellite and surface measurements is supported by the elastic properties of the lithosphere and by the underlying mantle convection. Three dimensional shear wave velocities can be determined by tomographic inversion of surface wave velocitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…In fact, the areas of greatest recent uplift and volcanism in Anatolia are those where we infer an introduction of subslab material into the Anatolian asthenosphere, either vertically through the Cyprus slab tear or laterally through the slab gap (Figure 10, Section 5.4). This suggests that any hot material being introduced originates below the African slabs, perhaps part of a regional North African/Mediterranean upwelling (Nikogosian et al., 2018) or simply a background ‘spoke‐pattern’ mantle convection pattern that has been suggested to occur in the region (Lees et al., 2020; McKenzie, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the areas of greatest recent uplift and volcanism in Anatolia are those where we infer an introduction of subslab material into the Anatolian asthenosphere, either vertically through the Cyprus slab tear or laterally through the slab gap (Figure 10, Section 5.4). This suggests that any hot material being introduced originates below the African slabs, perhaps part of a regional North African/Mediterranean upwelling (Nikogosian et al., 2018) or simply a background ‘spoke‐pattern’ mantle convection pattern that has been suggested to occur in the region (Lees et al., 2020; McKenzie, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamically modified anomalous topography and plate-mantle interaction in the eastern Mediterranean region have been investigated by using a range of numerical modeling approaches (e.g., Bartol & Govers, 2014;Boschi et al, 2010;, 2020Faccenna et al, 2014;Komut, 2015;Komut et al, 2012;Uluocak et al, 2016;van Hunen & Allen, 2011). However, the role of active mantle processes is still an open question in the Arabian-Eurasian plate convergence zone mainly because of the poorly constrained/resolved data and/or the lack of 3D variations of the regional processes (such as, 3D upper mantle structures in relation to the lithospheric thickening processes beneath the eastern Anatolia).…”
mentioning
confidence: 99%
“…the region has a wide range of crustal (∼30-50 km,Delph, Biryol, et al, 2015;Karabulut et al, 2019;Zor, 2008) and lithospheric depths (∼52-146 km, e.g.,McKenzie, 2020;McKenzie & Priestley, 2008;Motavalli-Anbaran et al, 2016;Priestley et al, 2012;Priestley & McKenzie, 2013;Skobeltsyn et al, 2014), we simplify the physical model with average values for the crust and lithosphere (40 and 80 km, respectively) to avoid isostatic effects that might be caused by lateral variations of the compositional fields (e.g.,Shaw & Pysklywec, 2007). The reference density contrast (ρ 0 , Model-1, Table1) between the lithosphere and underlying sublithospheric (asthenospheric) mantle is set to 1.2% (e.g.,Faccenna et al, 2014. Due to the uncertainties of densities arising from changing compositional aspects of the materials (i.e., crust, lithosphere, and mantle), we also test different density parameters (i.e., Model-3 for ρ 1 and Model-4 for ρ 2 ,Faccenna et al, 2014; Karabulut et al, 2019, respectively) and wet olivine rheology beneath the crust…”
mentioning
confidence: 99%
“…On the inner side of the arc was another large area of thin and weak lithosphere. McKenzie (2020) confirmed that the present lithosphere there is indeed quite thin as its thickness is less than 70‐50 km. Note that the area of weak lithosphere extends to the south to eastern Africa and Arabia which correspond to what Şengör et al.…”
Section: Lithospheric Structure Of Pangeamentioning
confidence: 78%